The effects of retrofitting RC frames by X-bracing on the seismic performance of columns. (15th October 2018) - Rahimi, A; Maheri, Mahmoud R.
Highlights: The adverse effects on performance of columns in RC frames retrofitted by X-bracing is investigated. Nonlinear time history analyses are used to study retrofitting effect on shear and axial forces and fatigue life. The X-bracing is beneficial to the performance of RC columns in low-rise frames. The performance of columns adjacent to bracing system is adversely affected in mid to high rise frames. The low-cycle fatigue may increase demand on RC columns in mid to high rise frames. Abstract: One of the common method for retrofitting RC frames is to use steel braces. The majority of reported research related to steel bracing of RC frames have highlighted the positive effects of bracing such as improving structural performance, increasing shear capacity, reducing displacements and decreasing drifts. Very little is reported on the possible side effects of the technique on the RC members, particularly those of columns. This papers aims at evaluating, through time history analyses, the behaviour of RC columns before and after retrofitting with steel X-bracing and examining possible complications, increased demands and side effects of such a retrofitting method. The effects on the level of column shear and axial force, as well as, column performance level and low cycle fatigue life are investigated. As a general conclusion, it is found that retrofitting low-rise RC frames with steel X bracing is beneficial to the performance of frame columns in almost every aspect; however, for mid to high-rise frames, the adverse effects of retrofitting, particularly on columns attached to the bracing system, are considerable and should be taken into consideration and if needed, local strengthening of columns should simultaneously be undertaken.